Exploring Fish Biodiversity and the Socioeconomic Status of Fishers in the Karatoya River, Sadar Upazila, Panchagarh District, Bangladesh - Alam, Md. Arfin; Rahman, M. Aminur; Jinia, Sharmin Sultana; Biswas, Sabnil; Mojumdar, Shoumik; Yeasmine, Selina; Akter, Sumi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
These studies were carried out to study species diversity of fishes and socio-economic conditions of the fishers of Karatoya River at Sadar upazila in Panchagarh district Bangladesh. Pertinent information was collected from 65 fishermen, who were directly engaged in catching fish around the study area for six months from December 2022 to June 2023. The results demonstrated that 41 fish species belonging to 8 orders and 15 families were found in the Karatoya River. Cypriniformes was found as the most dominant order, constituting 50.6% of the total fish population, considering species abundance, and Siluriformes constituting 12.7% and Perciformes constituting 12.0%, which were occupied the second and third position in abundance. The order Channiformes, Clupeiformes, Mastacembeliformes and Tetraodontifomres were constituted 6.6%, 6.0%, 4.8%, and 4.2%, respectively. Beloniformes constituted the lowest number of species (30%). It was observed that many fish species in the Karatoya River were severely impacted by the environmental and human-induced hazards. However, the age of the fishermen was ranged from 22 to 65 years. The Hindus (70%) were featured to be the highest percentage than the Muslims (30%), while no Christians and Buddhists were found. Various levels of education were documented in the study area, where majority of the fishermen were illiterate (69%), up to primary 18%, up to secondary 8% and the small portion (5%) were above secondary. The fishermen’s housing status was predominated by kaccha (66%), followed by semi pacca (23%) and pacca (11%). Majority of the fishers were landless (39%), whereas 15% fishers had 1-10 decimal (dec.) lands, 18% had 11-20 dec., 11% had 21-30 dec., 14% had 31-40 dec. and badly 3% of them had possessed >40 dec. lands. Among the fishermen, 45% of them were found to be involved in fishing activities, 40% in agriculture and 15% in sand business as day-to-day labour. There were 4 types of nets, 3 types of traps, 4 types of spears and 2 types of line fishing operated in this area. The study revealed that the fisheries production was not sufficient according to the demand. The reasons behind this might be due to the fact that the fishers around the Karatoya River were mainly poor, illiterate, lack of proper training and also nonexistence of consciousness of their sanitary and health care facilities. Therefore, it is very important to provide the required Organizational and Institutional help, support and extension facilities for the enhancement of fish biodiversity as well as development of sustainable livelihood of fishers in the Karatoya River as well.